(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
This article will talk about alternative energy sources and their types. It is mentioned that the currently most sophisticated alternative energy types available are solar, wind, bioenergy and geothermal energy types. It is also stated that they have advantages over their convenience, other traditional types. It is said that in the future, these types of energy will be effectively used as the main sources of energy in all areas of the human lifestyle.